PERAN PENDIDIKAN KOMUNITAS DALAM MENINGKATKAN BUDAYA LITERASI ANAK USIA SEKOLAH DASAR: STUDI KASUS TERHADAP TAMAN BACAAN MASYARAKAT DI LOMBOK TENGAH - Arif Widodo; Ashar Pajarungi Anar; Nursaptini Nursaptini; Deni Sutisna; Muhammad Erfan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Literacy is not only the responsibility of formal education institutions. One form of education in society is a community library. This study aimed to describe the roles and problems faced by community library forums in enhancing literacy culture. The subject in this study was a community reading garden as a part of a community library forum. Data were collected in Kabupaten Lombok Tengah. This study applied a qualitative research design with a case study approach. Data collection was conducted through surveys, observation, and in-depth interviews. Then, the data were presented in the form of tables, diagrams, and word descriptions. The researchers extended the observation time in order to achieve the validity of findings. The main problems found in this study included: what are the challenges faced by community library forums? What is the role of the community library forum in enhancing the literacy culture of children in Lombok Tengah? The results revealed that the challenges faced by community library forums included problems of regeneration, inadequate facilities, lack of book collections, low literacy culture, and non-optimal support from the government. The role of libraries in enhancing literacy culture was as a facilitator, motivator, creator, and pioneer of the literacy movement in rural areas. With the presence of the community library, the children felt more excited about reading.